Antibacterial and antibiofilm activities of kaffir lime essential oils and their active constituents against Staphylococcus aureus focusing on sortase A - Chayapol Pontanayodsakorn; Chatchakorn Eurtivong; Pimsumon Jiamboonsri (Heliyon)
Staphylococcus aureus biofilm has become a global medical concern due to rising antibiotic resistance. This study aimed to evaluate the potential activities of kaffir lime essential oils and their active compounds as alternative anti-S. aureus biofilm agents. The compositions of the essential oils were identified by gas chromatography/mass spectrometry (GC/MS), and their antibacterial activity was determined through broth-microdilution and time-kill assays. Antibiofilm activities were assessed using Congo red agar (CRA) well diffusion method, pre-biofilm inhibition resazurin assay, and post-biofilm inhibition assay. Sortase A (SrtA) inhibition was also investigated using in silico and in vitro approaches. This is followed by morphological studies to observe change in biofilm formations using light and scanning electron microscopy (SEM). Phytochemical analysis revealed that the kaffir lime essential oils from leaves (KLL) and peels (KLP) were primarily composed of the monoterpene aldehyde citronellal (59.13 %) and the monoterpene hydrocarbon (−)-limonene (25.69 %). However, the monoterpenoid alcohols, β-citronellol and terpinen-4-ol, which were the third most abundant compounds in KLL (5.35 %) and KLP (10.87 %), respectively, were selected for further study. All test compounds exhibited anti-Staphylococcal activity with a minimum inhibitory concentration (MIC) range of 0.1–0.3 % v/v. Their inhibition above the MIC levels showed time- and concentration-independence. Among the test compounds, terpinen-4-ol revealed good antibiofilm activity by inhibiting biofilm formation rather than eradicating the established biofilm. However, terpinen-4-ol exhibited weak SrtA inhibition with docking score of 32.58 and in vitro SrtA inhibition of 46.14 ± 3.58 % at 1 % v/v. Interestingly, terpinen-4-ol caused visible damage to the bacterial cell barrier, as revealed by SEM micrographs. These findings suggest the potential use of kaffir lime oils and their active compounds to combat biofilm-forming S. aureus infection.